2019
DOI: 10.1039/c9cp90226k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Surface heterogeneity and inhomogeneous broadening of vibrational line profiles

Abstract: Correction for ‘Surface heterogeneity and inhomogeneous broadening of vibrational line profiles’ by Skandar Taj et al., Phys. Chem. Chem. Phys., 2017, 19, 7990–7995.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, we found that another scenario might be more attractive. Indeed, experiments on CO adsorption on water ices show the presence of a specific band at 2,152-2,153 cm −1 in the case of CO adsorption in pores compared to a band at 2,139 cm −1 for surface adsorption sites (Fraser et al, 2004;Taj et al, 2017Taj et al, , 2019. The relatively sharp band that we observed at 2,153 cm −1 might well be due to CO entrapped in the porous dust (cf.…”
Section: Dust Infrared Spectroscopymentioning
confidence: 51%
“…However, we found that another scenario might be more attractive. Indeed, experiments on CO adsorption on water ices show the presence of a specific band at 2,152-2,153 cm −1 in the case of CO adsorption in pores compared to a band at 2,139 cm −1 for surface adsorption sites (Fraser et al, 2004;Taj et al, 2017Taj et al, , 2019. The relatively sharp band that we observed at 2,153 cm −1 might well be due to CO entrapped in the porous dust (cf.…”
Section: Dust Infrared Spectroscopymentioning
confidence: 51%
“…However we found that another scenario might be more attractive. Indeed, experiments on CO adsorption on water ices show the presence of a specific band at 2152-2153 cm −1 in the case of CO adsorption in pores compared to a band at 2139 cm −1 for surface adsorption sites (Fraser et al, 2004;Taj et al, 2017Taj et al, , 2019. The relatively sharp band that we observed at 2153 cm −1 might well be due to CO entrapped in the porous dust (cf.…”
Section: Impact Of Metals On (Star)dust Chemistrymentioning
confidence: 55%
“…The inversion technique of Kay and co-workers [164][165][166] has been widely adapted to describe small molecule desorption from many heterogeneous astrophysically-relevant surfaces including carbonaceous [174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189], siliceous [101,[169][170][171]181,[190][191][192][193][194][195] and ice surfaces [196,197]. But we are now beginning to see the extended inversion method of Smith et al…”
Section: Thermal Processesmentioning
confidence: 99%